Translating Emirati Folklore - Al Khamiri, Shaikha H. (2015)
A Master of Arts thesis in Translation and Interpreting MATI (English/Arabic/English) by Shaikha H. Al Khamiri entitled, "Translating Emirati Folklore," submitted in December 2015. Thesis advisor is Dr. Said Faiq. Soft and hard copy available.